Chromosomal Locations and Interactions of Four Loci Associated With Seed Coat Color in Watermelon - Paudel, Lucky; Clevenger, Josh; McGregor, Cecilia (Frontiers in Plant Science, 2019)
Different species of edible seed watermelons (Citrullus spp.) are cultivated in Asia and Africa for their colorful nutritious seeds. Consumer preference vary for watermelon seed coat color. Therefore, it is an important consideration for watermelon breeders. In 1940s, a genetic model of four genes, R, T, W and D, was proposed to elucidate the inheritance of seed coat color in watermelon. In this study, we developed three segregating F2 populations: Sugar Baby (dotted black seed, RRTTWW) x plant introduction (PI) 482379 (green seed, rrTTWW), Charleston Gray (dotted black seed, RRTTWW) x PI 189225 (red seed, rrttWW) and Charleston Gray (dotted black seed, RRTTWWdd) x UGA147 (clump seed, RRTTwwDD) to re-examine the four-gene model and to map the four genes. In the dotted black x green population, the dotted black seed coat color (R_) is dominant to green seed coat color (rr). In the dotted black x red population, the dominant dotted black seed coat color and the recessive red seed coat color segregate for the R and T genes, where the R gene is dominantly epistatic to the T gene. However, the inheritance of the T locus did not fit the four-gene model, thus we named it T1. In the dotted black x clump population, the clump seed coat color and the dotted black seed coat color segregate for W and D, where D is recessively epistatic to W. The R, T1, W and D loci were mapped on chromosomes 3, 5, 6 and 8, respectively using QTL-seq and genotyping-by-sequencing (GBS). Kompetitive Allele Specific PCR (KASPTM) assays and SNP markers linked to the four loci were developed to facilitate maker-assisted selection (MAS) for watermelon seed coat color.